Does public spending structure affect the efficiency of spending? Evidence from a panel tobit model for Chinese provinces - Zhirong Ou; Fuwen Zeng; Xinyu Zhan (International Journal of Management, Economics and Social Sciences (IJMESS), 2020)
The general financial stress confronting Chinese local governments requires public spending to become more efficient. While previous work has attempted to study what determines the efficiency, the focus was put on various factors that were not under direct control by policymakers. This paper revisits the issue, controlling the factors commonly found to be significant in the literature, by evaluating the role of the spending structure which can be easily adjusted by policymakers. The paper focuses on the investment ratio, as public investment is known to be a key driver of the Chinese economy. Using data of 31 provinces between 2000 and 2017, we estimated a Tobit model, with the efficiency of public spending calculated by data envelopment analysis (DEA). The efficiency of public spending is partially determined by the structure of the spending; the former is an increasing function of the latter up to an optimal rate, which is estimated to be between 19-23 percent. As most local governments are over-investing according to this standard, future improvement of budget management would require policymakers to concentrate much more on non-investment projects, such as spending on benefits, education and healthcare - hence, the provision of public goods and services.
Keywords: D61; H11; 330; Efficiency; public spending; data envelopment analysis (DEA); panel Tobit model; China